Breastfeeding performance in Afar regional state, northeastern Ethiopia: a cross sectional study - Jemal Hussien; Selam Assefa; Misgan Legesse Liben (BMC, 2018)
Abstract Background In Ethiopia fewer than 20% of infants aged less than six months are appropriately fed. This study aimed to identify predictors of poor breastfeeding performance among mother-infant pairs in Samara-Logia city administration, Afar Regional State, Ethiopia. Methods Five hundred and seventy six mothers of infants aged less than six months were recruited to participate in face-to-face structured interviews at their home. Infant feeding practices were measured by breastfeeding performance index (BPI). Infants who scored 0-3 BPI were classified as achieving 'Low BPI', 4-5 as 'Medium BPI', and 6-7 scores as 'High BPI'. A pre-tested instrument was used to assess demographic characteristics of mothers and their experiences of infant feeding. EpiData version 3.02 was used to enter, clean and code the data. Then, data were analyzed using SPSS version 20. Results Five hundred thirty six (93.1%) of the study mothers had ever breastfed their infants. About 83% [95% CI: 80.0, 86.0%] of infants had achieved low or medium BPI scores. Being older than 34 years [AOR: 4.55; 95% CI (1.33, 15.73)], having an infant aged 4-5 months [AOR: 2.49; 95% CI (1.08, 5.76)], giving birth at home [AOR: 4.25; 95% CI (1.37, 13.23)] or by caesarean section [AOR: 8.00; 95% CI (2.78, 23.09)] and receiving advice on proper infant feeding practices at postnatal checkup [AOR:0.28; 95% CI (0.13,0.59)] were independent predictors of low/medium BPI scores. Conclusion This study revealed that nearly eight in ten infants aged less than six months achieved low/medium BPI scores. Being older than 34 years, having an infant aged 4-5 months, giving birth at home or by caesarean section and lack of advice on proper infant feeding practices were associated with higher odds of low/medium BPI scores.